Effect of HIV-1 and antiretroviral therapy on herpes simplex virus type 2: a prospective study in African women. Issue 5 (2nd July 2008) - Mayaud, P; Nagot, N; Konaté, I; Ouedraogo, A; Weiss, H A; Foulongne, V; Defer, M-C; Sawadogo, A; Segondy, M; Van de Perre, P
Abstract : Objectives: To document the natural history of herpes simplex virus type 2 (HSV-2) in relation to HIV and highly active antiretroviral therapy (HAART) in Africa, a longitudinal study was conducted of women in the placebo arms of two randomised controlled trials of HSV-suppressive therapy in Burkina Faso. Methods: 22 HIV-uninfected women (group 1), 30 HIV-1-infected women taking HAART (group 2), and 68 HIV-1-infected women not eligible for HAART (group 3) were followed over 24 weeks. HSV-2 DNA was detected on alternate weeks using real-time PCR from cervicovaginal lavages. Plasma HIV-1 RNA was measured every month. CD4 cell counts were measured at enrolment. Results: Ulcers occurred on 1.9%, 3.1% and 7.2% of visits in groups 1, 2 and 3 (p = 0.02). Cervicovaginal HSV-2 DNA was detected in 45.5%, 63.3% and 67.6% of women (p = 0.11), and on 4.3%, 9.7% and 15.5% of visits in the three groups (p<0.001). Among HIV-infected women, cervicovaginal HSV-2 DNA was detected more frequently during ulcer episodes (adjusted risk ratio (aRR) 2.79, 95% CI 2.01 to 3.86) and less frequently among women practising vaginal douching (aRR 0.60, 95% CI 0.40 to 0.91). Compared with women not taking HAART and with CD4 cell counts of 500 cells/μl or greater, women on HAART had a similar risk of HSV-2 shedding (aRR 0.95, 95% CI 0.52 to 1.73), whereas women with CD4 cell counts of 200–500 cells/μl were more likely to shed HSV-2 (aRR 1.71, 95% CI 1.02 to 2.86). Conclusions: HSV-2 reactivations occur more frequently among HIV-infected women, particularly those with low CD4 cell counts, and are only partly reduced by HAART. HSV therapy may benefit HIV-infected individuals during HAART.